Embracing Vulnerability In The Midst Of Danger: Therapy In A High Secure Prison (Existential Analysis: Journal of the Society for Existential Analysis, 2018)
Within British society, a clear need to dehumanise offenders and see them as 'other' hampers efforts to rehabilitate. Difficulties in perceiving the vulnerability of those who are incarcerated, even by psychologically-trained staff who work within prisons, shape the interventions that are available to prisoners and may prevent innovation that could enable therapeutic growth and ultimately reduce risk. This paper explores how a willingness to engage with the prisoners' vulnerability in terms of their traumatic histories leads to significant higher levels of disclosure about childhood trauma and adversity and the opportunity to deliver meaningful therapy to men who are hard to reach and frightened to engage. The paper describes how one service based in a high secure prison is able to overcome barriers to participation in treatment by adopting a trauma-focused approach.
Keywords: Prison; offending; personality disorder; trauma-focused; psychological treatment